Importance of fatiguing, overtraining and chronic fatigue in athletes - Adam Piesik; Monika Dryja; Monika Zawadka-Kunikowska; Joanna Slomko; Mariusz Kozakiewicz; Małgorzata Tafil-Klawe; Jacek J. Klawe; Paweł Zalewski (Kazimierz Wielki University, 2017)
Each training that requires achieving a higher heart rate limit and/or increased concentration in time may cause fatigue, considered to be a natural defence mechanism of a body. In the case of excessive fatigue and insufficient time designated for rest and regeneration, an overtraining syndrome (OTS) may develop. The main symptom of overtraining is increased fatigue that fails to become reversed in normal conditions of regeneration. Although authors are familiar with the overtraining syndrome and associated symptoms, as of today no diagnostic tool has been developed that may form a basis for a final diagnosis, and the diagnosis itself is frequently based on a subjective assessment of the athlete. Possible causes of the band overtraining syndrome are disorders of sodium, inflammatory processes resulting from physical activity and / or disorders of the autonomic nervous system.